Remote supervision of teacher trainee internships: Using digital technology to increase social presence - Petit, Matthieu; Babin, Julie; Desrochers, Marie-Ève (Frontiers in Education, 2023)
When digital technologies are used to supervise teacher trainees, internship supervisors adjust their practices to enhance their presence within their cohort in order to reduce the isolation felt by those who choose to do their internship locally, when home is in a remote location from their campus or university. In this article, we will share findings about the concept of social presence through a description of practices according to three indicators from the online community of inquiry theoretical model: emotional expression, open communication and group cohesion. From a qualitative methodology, our results attest to the humanistic nature of the remote supervision. During their online interactions with trainees, the internship supervisors interviewed share their feedback about videos and graded work tactfully, bearing in mind the distance that separates them. Despite how difficult it is to show empathy in mediated communication, they try by many means, including video and immediacy, to comfort trainees who may feel alone. They offer them frequent practical support and check in with them at the beginning and throughout the internship. Their support is bolstered by the authenticity of the situations observed in video footage, above and beyond the institutional systems.